Influence of layering sequences on tensile properties of hybrid woven Jute/Ramie fibre reinforced polyester composites - Tezara, C.; Siregar, Januar Parlaungan; Mohammad Hazim, Mohammad Hamdan; T., Rihayat; Bachtiar, Dandi; Fitriyana, Deni Fajar; Prayitno, P. (Elsevier Ltd, 2021)
Many researchers around the globe have shifted their focus onto the renewable resources lately. This trend is due to the number of resources that are almost reaching its critical stage hence the exploration of natural fibre composites has also caught the world’s attention. In this research the effect of the number of layers, stacking sequences, and orientation of plain weave jute and ramie fibre single/hybrid composites on tensile properties were investigated. The stacking sequences consisted of two and three layered of laminated composite of pure jute (JJ, JJJ), pure ramie (RR, RRR) and ramie/ramie/ramie (RRR), whereas jute/ramie (JR), jute/jute/ramie (JJR), jute/ramie/jute (JRJ), ramie/jute/ramie (RJR), jute/ramie/ramie (JRR) were included under the hybrid composites category. The comparisons of tensile properties for each of the pure polyester, single, and hybrid composites were evaluated afterwards. The tensile strength and tensile modulus of the composites that was constructed with different fibre direction of warp and weft for each layer were also analyzed. The hand lay-up method was employed for all the fabrication of the composite specimens. From the results, it was observed that the tensile properties of the skin-core type composites (RJR, JRJ) have showed a better performance compared to the skin-eccentric types (RRJ, JJR) with similar ramie content. Attributed to a good fibre rigidity of Ramie fibre, the tensile strength and tensile modulus values could be enhanced with the addition of the ramie content in the composite mixture. The tensile properties were proven to also be improved with the increase number of woven layers in the composite. The Jute/ramie hybrid composite has exhibited very high potential in the future development of the automotive industry.